Urgensi Kewenangan Pemerintah dalam Penanganan Pencemaran Lingkungan untuk Perlindungan Kesehatan Masyarakat di Indonesia - admin; Feda Rifandhana, Raditya; Rahadian Wicaksono, Rizky; Yudha Bramantyo, Rizki; Krishna Wistara, Agantoro; Sri Wulandari , Maulidia; Wildan Rifqy, Mohammad; Muliati, Oktaviani (Jurnal EnviScience (Environment Science), 2025)
A polluted environment has various negative impacts on public health. Air, water, and soil pollution in Indonesia are often caused by weak oversight and suboptimal government authority in controlling environmental pollution. Therefore, the government has a strategic role to ensure a healthy environment through strict environmental policies and law enforcement. This study aims to examkeine the urgency of government authority in addressing environmental pollution as an effort to protect public health. The research method uses a normative approach with legal theory as an analytical tool, packaged in the form of a descriptive analysis of regulations and their implementation in the field.